1955
DOI: 10.1071/ar9550804
|View full text |Cite
|
Sign up to set email alerts
|

A study in rate of pasture growth

Abstract: The growth curve of a pasture consisting of short-rotation ryegrass, red clover, and white clover was determined by measuring dry matter yields at intervals over a 9-week period in the spring of 1953. To determine the effects of temporary weather variations on growth, the experiment was replicated in time as well as space. The experimental technique is described. The curves of growth for ryegrass and total herbage were sigmoid. In the second phase of growth of approximately 6 weeks when rate of growth was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
17

Year Published

1959
1959
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 0 publications
3
41
0
17
Order By: Relevance
“…As taxas de crescimento da planta estão relacionadas com a área foliar remanescente e, consequentemente, à quantidade de luz interceptada pelas folhas (BroughaM, 1955). Este mesmo autor descreveu as fases da rebrota em plantas de clima temperado, que se assemelham às respostas obtidas em estudos com plantas de clima tropical.…”
Section: Intensidade E Frequência Do Pastejounclassified
“…As taxas de crescimento da planta estão relacionadas com a área foliar remanescente e, consequentemente, à quantidade de luz interceptada pelas folhas (BroughaM, 1955). Este mesmo autor descreveu as fases da rebrota em plantas de clima temperado, que se assemelham às respostas obtidas em estudos com plantas de clima tropical.…”
Section: Intensidade E Frequência Do Pastejounclassified
“…Brougham [10] fitted a sigmoid curve to the variation in herbage mass during regrowth of perennial ryegrass (Lolium perenne L.), white clover (Trifolium repens L.) and red clover (Trifolium pratense L.) mixed swards (variation in herbage mass with time), as well as describing the asymptotic relationship between LAI and LI [12,17]. The author demonstrated that plant growth was a function of canopy light interception and LAI, and that the rate of herbage dry matter accumulation reached a maximum constant value when there was enough foliage to intercept almost all the incident light.…”
Section: Forage Grass Research-a Historical Overviewmentioning
confidence: 99%
“…The authors concluded that during the vegetative growth stage the 95% LI criterion could be used to define the best moment for initiating defoliation and, relative to longer defoliation intervals, would result in greater herbage production with higher proportion of leaves and lower proportion of dead material. That would indicate the ideal harvest point during regrowth (determinant of cutting and/or grazing interval), a condition that would be associated with the end of the linear phase of the sigmoidal growth curve described by Brougham [10]. These findings indicated convergence of the available knowledge and corroborated the central role of LAI as a determinant of plant responses to grazing, highlighting the need to study and understand aspects related to sward structure, light use, and the balance between growth and senescence as a means of planning and defining efficient grazing management strategies [67].…”
Section: Forage Grass Research-a Historical Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the generalised increment for the ith week of growth is estimated from data on the ith week and data 2, 4, and 6 weeks later, the date on which this increment would be obtained under a smoothly changing season can be taken as week (i + 3). Also, because the parameters are obtained for constant weather over 12 weeks, the trends in growth owing to gradual changes in season appear as trends in the W parameters, and in the earlier work (Brougham 1955) these trends were themselves separated and added to the g parameters to give theoretical curves of growth for smoothly changing climate.…”
Section: Methodsmentioning
confidence: 99%